A synchrotron radiation high-resolution soft X-ray lens and its preparation method
By using low absorption metal oxide materials and electron beam lithography and ALD processes, high-resolution soft X-ray waveband lenses were prepared, solving the problem of low efficiency of traditional focusing lenses and achieving high-efficiency focusing and imaging of soft X-ray bands.
Patent Information
- Application Number
- CN202111486120.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-07
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-12-07
AI Technical Summary
Traditional soft X-ray band focusing lenses have low efficiency and difficult process preparation, making them difficult to meet the needs of high resolution and high efficiency.
High-resolution soft X-ray waveband lenses are prepared by electron beam lithography and atomic layer deposition (ALD) technology.
The focus efficiency of the soft X-ray band is improved, from the theoretical limit value (10%) of the traditional wave band sheet to 15%, and the process is stable and reliable, suitable for a variety of application scenarios.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of micro-nano processing, and in particular relates to a synchrotron radiation high-resolution soft X-ray lens and a preparation method thereof. Background Art
[0002] Synchrotron radiation X-ray microscopy is one of the important methods for current research in basic disciplines such as materials, physics, biology, and medicine. X-ray focusing optical elements are a crucial component in X-ray imaging systems. In soft X-rays (0-2keV), especially in the water window band (280~530eV) that has natural contrast for biological imaging, traditional diffraction focusing lenses based on metal Fresnel zone plates (FZP) have a large absorption coefficient in this band, resulting in actual focusing efficiencies of less than 5%.
[0003] In order to break the bottleneck of low efficiency and difficult process preparation of focusing lenses in the soft X-ray band, the present invention proposes to use metal oxide materials with low absorption rate in the soft X-ray band (0-2keV) as lens dielectric materials, and prepare high-resolution and high-efficiency soft X-ray zone plate lenses by electron beam lithography and atomic layer deposition (ALD) methods. In the soft X-ray band, the focusing efficiency can theoretically be increased from the theoretical limit value (10%) of traditional zone plates to 15%. The design and processing scheme has good reliability and can prepare a series of zone plate lenses with different diameters and resolutions to meet the needs of different application scenarios. High-resolution and high-efficiency focusing in the soft X-ray band will have broad application prospects in multiple X-ray optical fields such as synchrotron radiation micro-nano probes, full-field microscopy, X-ray confocal microscopy and new X-ray fluorescence CT, which will greatly improve the level of synchrotron radiation detection technology in my country and is of great significance to my country's basic discipline research.
[0004] This process is not only suitable for the preparation of zone plate lenses in the soft X-ray band, but can also be used for the preparation of other focusing and imaging elements at this energy. Summary of the invention
[0005] The purpose of the present invention is to provide a simple, stable and efficient synchrotron radiation high-resolution soft X-ray lens and a preparation method thereof.
[0006] The synchrotron radiation high-resolution soft X-ray lens proposed in the present invention has the following structures from bottom to top: a silicon substrate, a silicon nitride diaphragm, and an X-ray lens (hereinafter referred to as the lens) composed of a template material and a non-metallic dielectric material; wherein the X-ray lens is prepared by electron beam lithography and ALD processes; the silicon substrate and the silicon nitride diaphragm respectively play supporting and light-transmitting roles, and the front of the X-ray lens is placed on the silicon nitride diaphragm; the convergence direction of the lens is perpendicular to the silicon nitride diaphragm; the soft X-rays pass through the silicon nitride diaphragm and are focused behind the lens; the non-metallic dielectric material has a low absorption coefficient and can achieve high-resolution focusing of the soft X-rays.
[0007] In the present invention, the material for preparing the lens is a non-metallic material, which has low absorption in the soft X-ray band and has phase control capability, and is applicable to the ALD process. The non-metallic material includes but is not limited to silicon dioxide, hafnium oxide, and aluminum oxide.
[0008] In the present invention, the template material of the lens is a photoresist or other material having a low absorption rate for soft X-rays (0-2keV) and suitable for ALD process, including but not limited to HSQ and silicon.
[0009] In the present invention, within a single period of the lens template, the ratio of spaces to lines is 2.5-4, preferably 3-3.5, and more preferably 3.
[0010] In the present invention, the lens is fixed by reinforcing ribs, which are distributed in a spider web pattern; the line width of the reinforcing ribs is similar to the line width of the corresponding period, and the mutual spacing of the reinforcing ribs in the same period is 5 to 15 times the line width.
[0011] The present invention provides a method for preparing a synchrotron radiation high-resolution soft X-ray lens based on electron beam lithography and ALD process, and the specific steps are as follows:
[0012] (1) Spin coating HSQ photoresist on a substrate with a silicon nitride diaphragm;
[0013] (2) forming a photoresist pattern of a lens on the photoresist by electron beam lithography;
[0014] (3) developing the sample obtained in step (2);
[0015] (4) growing a non-metallic material on the sample obtained in step (3) using an ALD process;
[0016] (5) preparing a beam blocker by overlaying the sample obtained in step (4);
[0017] (6) Perform lift-off on the sample obtained in step (5).
[0018] In step (1) of the present invention, the preheating temperature before gluing is 200-280° C., and the preheating time is 5-10 min.
[0019] In step (2) of the present invention, the outermost ring period of the HSQ photoresist pattern is 40-240 nm, the diameter is 50-1000 um, and the line exposure dose is 4000-18000 μC / cm 2 , the central part of the lens is 4000~5000μC / cm 2 , the middle part is 6000-12000μC / cm 2 , peripheral 12000-18000μC / cm2 .
[0020] In step (3) of the present invention, the ratio of the developer is TMAH:H2O=1:3, the developing temperature is 60-85°C, and the developing time is 2-5 minutes. The fixing solution is water, the fixing temperature is 60-85°C, and the fixing time is 30s-120s.
[0021] In step (4) of the present invention, the thickness of the ALD-grown non-metal is 10-60 nm.
[0022] In step (4) of the present invention, in order to compensate the line to an ideal width, ALD can be used to supplement the growth of silicon dioxide according to the error.
[0023] In step (5) of the present invention, the beam blocker is prepared by window overlay combined with thermal evaporation; the thickness of PMMA is 2-5 μm; the post-baking temperature is 180°C, the post-baking time is 20-60 min; the exposure dose is 1000-2500 μC / cm 2 ; The developer is IPA:H2O=7:3, the developing temperature is 20--25℃, and the developing time is 2~4 min; the fixing solution is water, and the fixing time is 30s; the thickness of thermally evaporated Au is 300~1000 nm.
[0024] In step (6) of the present invention, the Lift-Off solution is acetone, and the Lift-Off temperature is 50-60°C; the cleaning solution is water, the cleaning temperature is 60°C, and the cleaning time is 25-60s.
[0025] Compared with the prior art, the method of the present invention has the following beneficial effects:
[0026] First, the present invention adopts a preparation method based on electron beam lithography and ALD process to obtain a soft X-ray lens. Compared with the traditional method of electron beam lithography combined with electroplating, the present invention has the advantages of simple and fast process.
[0027] Second, the present invention has good stability for the preparation of soft X-ray lenses. The ALD process can compensate the lines of electron beam lithography to an ideal width by growing silicon dioxide, so the present invention has a certain tolerance for the line accuracy of electron beam lithography.
[0028] Third, the present invention uses non-metallic media (hafnium oxide, aluminum oxide, etc.) with low absorption coefficient for soft X-rays as lens materials, and has higher diffraction efficiency in the soft X-ray band compared with traditional metal medium zone plates.
[0029] Fourthly, the lens dielectric material of the present invention is grown by the ALD process. Compared with the traditional electron beam lithography combined with electroplating method, the present invention has better control over the film thickness, can prepare a lens with a smaller outermost ring width, and has a higher resolution.
[0030] The method of the present invention can be used to prepare a high-resolution soft X-ray lens with non-metal as the dielectric material, and realize high-efficiency focusing and imaging of soft X-rays. In the soft X-ray band, the focusing efficiency can be increased from the theoretical limit value (10%) of the traditional zone plate to 15%. It has the advantages of stable and reliable process, shortened preparation cycle and compatibility with existing photolithography process. The prepared X-ray focusing imaging lens is particularly suitable for X-ray high-contrast three-dimensional imaging of materials with low contrast, such as biological cells, organic materials and dielectric materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the cross section of the ALD zone plate lens on the silicon nitride diaphragm.
[0032] Figure 2 This is a schematic diagram of the overall ALD zone plate lens on the silicon nitride diaphragm.
[0033] Figure 3 Corresponding to step 1: spin coating HSQ photoresist on the substrate.
[0034] Figure 4 Corresponding to step 2-3: After electron beam grayscale lithography and development, the HSQ zone plate lens pattern is obtained.
[0035] Figure 5 Corresponding to step 4: using the ALD process to deposit non-metallic material hafnium oxide on the HSQ zone plate lens.
[0036] Figure 6 Corresponding to step 5-6: a beam blocker is prepared on the HSQ zone plate lens after hafnium oxide deposition by using a thermal evaporation process and a lift-off process.
[0037] Figure 7 Corresponding to step 4: using the ALD process to deposit non-metallic material aluminum oxide on the HSQ zone plate lens.
[0038] Figure 8 Corresponding to step 5-6: a beam blocker is prepared on the HSQ zone plate lens after aluminum oxide deposition by using a thermal evaporation process and a lift-off process.
[0039] Fig. 9 SEM image of the hafnium oxide ALD zone plate lens corresponding to Example 1.
[0040] Fig.10A partial SEM image of the hafnium oxide ALD zone plate lens corresponding to Example 1.
[0041] Fig.11 X-ray imaging test results of the hafnium oxide ALD zone plate lens according to Example 1.
[0042] Fig.12 The curve showing the variation of theoretical efficiency of zone plate lenses made of different ALD materials with a height of 350nm as a function of energy. DETAILED DESCRIPTION
[0043] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but the present invention is not limited to the embodiments. Any simple changes to the process parameters in the embodiments fall within the scope of protection of the present invention.
[0044] Example 1. Preparation of 15nm resolution hafnium oxide ALD zone plate lens
[0045] (1) Select a silicon wafer with a silicon nitride window. The thickness of the silicon nitride window is 100nm and the size is 2mm×2mm;
[0046] (2) After the HMDS adhesion layer was spin-coated on the substrate, a 350 nm thick HSQ electron beam photoresist was spin-coated and baked in an oven at 220°C for 5 min to harden it. The results are shown in Figure 3 As shown;
[0047] (3) The sample was exposed under an electron beam lithography machine. The exposure pattern was a circular zone plate. The outermost ring period of the HSQ photoresist pattern was 60 nm, the ratio of gaps to lines was 3, and the diameter was 100 μm. The spacing between the reinforcing ribs of the same period was 8 times the line width. The exposure dose of the center part of the lens was 8000 μC / cm 2 , the exposure dose in the middle part is 10000~14000μC / cm 2 , peripheral exposure dose 16000μC / cm 2 ;
[0048] (4) After developing in a TMAH / H2O mixed solution with a volume ratio of 1:3 at 65°C for 4 min, the film was fixed in H2O at 85°C for 30 s. The results are as follows: Figure 4 As shown;
[0049] (5) The sample obtained in step (4) was grown with the ALD process to produce a 30 nm thick non-metallic material hafnium oxide. The results are as follows: Figure 5 As shown;
[0050] (6) Prepare a beam blocker by overlaying the sample obtained in step (4): Prepare the beam blocker by overlaying the window combined with thermal evaporation; the thickness of PMMA is 5 μm; the post-baking temperature is 180°C, and the post-baking time is 60 min; the diameter of the beam blocker is 50 μm, and the exposure dose is 2000 μC / cm 2 ; The developer is IPA:H2O=7:3, the developing temperature is 23℃, and the developing time is 4 min; the fixing solution is water, and the fixing time is 30s; the thickness of the thermally evaporated Au is 500 nm;
[0051] (7) Perform lift-off on the sample obtained in step (5). The lift-off solution is acetone, the lift-off temperature is 60°C; the cleaning solution is water, the cleaning temperature is 60°C, and the cleaning time is 60s. The results are as follows: Figure 6 shown.
[0052] The scanning electron microscope image of the actual prepared hafnium oxide ALD zone plate lens is shown in Figure 9-10 , the X-ray imaging test results at 1.2keV are as follows Fig.11 The resolution reached sub-20nm and the imaging efficiency was about 7.6%, which is close to the theoretical efficiency (10.8%). The main deviation is the adverse effect of the ribs and beam blocker on the efficiency. The above experimental test results further prove the feasibility of the process method.
[0053] Example 2. Preparation of 30nm resolution aluminum oxide ALD zone plate lens
[0054] (1) Select a silicon wafer with a silicon nitride window. The thickness of the silicon nitride window is 100nm and the size is 2mm×2mm;
[0055] (2) After spin coating the HMDS adhesion layer on the substrate, a 200 nm thick HSQ electron beam photoresist was spin coated and baked in an oven at 250°C for 5 min to harden it. The results are shown in Figure 2. Figure 3 As shown;
[0056] (3) The sample was exposed under an electron beam lithography machine. The exposure pattern was a circular zone plate. The outermost ring period of the HSQ photoresist pattern was 120 nm, the ratio of gaps to lines was 3.5, and the diameter was 100 μm. The spacing between the reinforcing ribs of the same period was 5 times the line width. The exposure dose of the center part of the lens was 8000 μC / cm 2 , the exposure dose in the middle part is 10000~14000μC / cm 2 , peripheral exposure dose 16000μC / cm 2 ;
[0057] (4) After developing in a TMAH / H2O mixed solution with a volume ratio of 1:3 at 65°C for 4 min, the film was fixed in H2O at 85°C for 30 s. The results are as follows: Figure 4 As shown;
[0058] (5) The sample obtained in step (4) was grown with 15 nm thick non-metallic aluminum oxide using the ALD process. The results are as follows: Figure 7 As shown;
[0059] (6) Prepare a beam blocker by overlaying the sample obtained in step (4): Prepare the beam blocker by overlaying the window combined with thermal evaporation; the thickness of PMMA is 3 μm; the post-baking temperature is 180°C, and the post-baking time is 60 min; the diameter of the beam blocker is 50 μm, and the exposure dose is 2000 μC / cm 2 ; The developer is IPA:H2O=7:3, the developing temperature is 23℃, and the developing time is 4 min; the fixing solution is water, and the fixing time is 30s; the thickness of the thermally evaporated Au is 300 nm;
[0060] (7) Perform lift-off on the sample obtained in step (5). The lift-off solution is acetone, the lift-off temperature is 60°C; the cleaning solution is water, the cleaning temperature is 60°C, and the cleaning time is 60s. The results are as follows: Figure 8 shown.
Claims
1. A method for preparing a synchrotron radiation high-resolution soft X-ray lens, characterized in that: The lens structure is, from bottom to top, silicon substrate, silicon nitride membrane, and an X-ray lens composed of a template material and a non-metallic dielectric material, hereinafter referred to as the lens; wherein the X-ray lens is prepared by electron beam lithography and ALD process; the silicon substrate and the silicon nitride membrane play supporting and light transmitting roles respectively, and the front of the X-ray lens is placed on the silicon nitride membrane; the convergence direction of the lens is perpendicular to the silicon nitride membrane; the soft X-rays pass through the silicon nitride membrane and are focused behind the lens; the non-metallic dielectric material has a low absorption coefficient, and can achieve high-resolution focusing of soft X-rays; The specific steps are as follows: (1) Spin coating HSQ photoresist on a substrate with a silicon nitride diaphragm; (2) forming a photoresist pattern of a lens on the photoresist by electron beam lithography; (3) developing the sample obtained in step (2); (4) growing a non-metallic material on the sample obtained in step (3) using an ALD process; (5) preparing a beam blocker by overlaying the sample obtained in step (4); (6) Lift-Off the sample obtained in step (5); In step (1), the preheating temperature before gluing is 200-280°C, and the preheating time is 5-10 minutes; In step (2), the outermost ring period of the HSQ photoresist pattern is 40~240 nm, the diameter is 50~1000 um; the line exposure dose is 4000~18000μC / cm 2 , the central part of the lens is 4000~5000μC / cm 2 , the middle part is 6000-12000μC / cm 2 , peripheral 12000-18000μC / cm 2 ; In step (3), the ratio of the developer is TMAH:H2O=1:3, the developing temperature is 60~85°C, and the developing time is 2~5min; the fixing solution is water, the fixing temperature is 60~85°C, and the fixing time is 30s~120s; In step (4), the thickness of the ALD-grown non-metal is 10 to 60 nm; In step (4), in order to compensate the line to the ideal width, ALD is first used to supplement the growth of silicon dioxide according to the error; In step (5), the beam blocker is prepared by window overlay combined with thermal evaporation; the thickness of PMMA is 2-5 μm; the post-baking temperature is 180°C, the post-baking time is 20-60 min; the exposure dose is 1000-2500 μC / cm 2 ; The developer is IPA:H2O=7:3, the developing temperature is 20--25℃, and the developing time is 2-4 min; the fixing solution is water, and the fixing time is 30s; the thickness of thermally evaporated Au is 300-1000 nm; In step (6), the Lift-Off solution is acetone, and the Lift-Off temperature is 50-60°C; the cleaning solution is water, the cleaning temperature is 60°C, and the cleaning time is 25-60s.
2. The preparation method according to claim 1, characterized in that: The non-metallic dielectric material for preparing the lens is selected from silicon dioxide, hafnium oxide and aluminum oxide.
3. The preparation method according to claim 1, characterized in that: The template material of the lens is a photoresist with low absorption rate for soft X-rays and suitable for ALD process.
4. The preparation method according to claim 1, characterized in that: The template material of the lens is selected from HSQ and silicon.
5. The preparation method according to claim 1, characterized in that: Within a single period of the lens template, the ratio of spaces to lines is 2.5~4.
6. The preparation method according to claim 1, characterized in that: The lens is fixed by reinforcing ribs, which are distributed in a spider web pattern. The line width of the reinforcing ribs is similar to the line width of the corresponding period, and the mutual spacing of the reinforcing ribs in the same period is 5 to 15 times the line width.
Citation Information
Patent Citations
X-ray zone plate and preparation method thereof
CN108806820A
Kinoform dielectric lens for synchrotron radiation soft X-ray focusing imaging and preparation method thereof
CN112885499A